State legal institutions and amicable settlement in the rural Philippines - Machado, Kit G. (1980)
A thorough investigation of personal disputes filed with the Batangas' Municipal Courts and Court of First Instance illustrated how and where the Philippine state legal institutions fit into the broader patterns of dispute-processing in rural Philippines. The examination revealed the low reliance on state adjudication and the strong dependence on "amicable settlement" in dispute-processing even among the most serious cases. Factors influencing dispute-processing were identified, L e., (1) the feature of the community where the dispute took place; (2) the interests and behavior of its politicians and local officials; (3) the costs and likely outcome of alternative means of dispute-processing; and (4) the intentions, prior relationships and comparative resources of disputants.
Keywords: Judicial process; Legal systems; Legal services -- Law and ethics; Justice administration -- Batangas